The Influence Of Taste and Product Quality to Purchasing Decisions and Customer Satisfaction: (Case study of consumers who buy Entrasol milk in Surabaya) - Feri Andrianto (Journal of World Conference (JWC), 2019)
This study is to analyze the influence of taste and product quality topurchasing decisions and customer satisfaction. Type of research is quantitive. The population of this study were 100respondents who bought Entrasol milk in Surabaya. The analysis technique used is Partial Least Square. Data obtained from questionnaires and tested with SmartPLS 3.0 application. The results of this study indicate that taste, and product quality have a positiveand significant influence on purchasing decision and customer satisfaction. Andpurchasing decision has a positive and significant effect on customer satisfaction.